Protocolo de Ayello para prevenção de úlcera por pressão na pessoa com lesão medular: avaliação da eficácia - Studart, Rita Mônica Borges (2013)
People with spinal cord injuries present high risk for developing pressure ulcers (PU) because of the chronicity, severity, and the average hospital stay, particularly for impaired physical mobility. The study aimed at evaluating the effectiveness of teaching protocol for prevention of PU in people with spinal cord injury. And as specific: identify the behavioral changes occurring in the companions from following the teaching protocol for prevention of PU, and investigate the impact of the teaching protocol in the reduction of the lesions. Experimental study type randomized clinicai trial with blinding conducted with 122 patients at a public emergency hospital in the city of Fortaleza from September 20'11 to October 2012. In this essay the researcher divided the cohort into two groups: the experimental group (EG) and control group (CG) composed of 61 patients each. Randomization was done by month, EG comprised patients hospitalized in the pairs months and patients for CG by patients hospitalized in odd months, regardless of the unit, so that kept the randomness of randomization. This study was approved by the Ethics and Research Committee of the Federal University of Ceará. Similarity was found between the groups and predominated for indicators: male (82%), age (median: 30 years), low education levei, family income below the poverty levei; Catholic (62.3%); autonomous; involvement lumbar with 40.9% in the EG and 49.1% in CG by car accident with 45.9% in the EG and 49.1% in the CG. Regarding companions who applied the protocol prevailed age 27-36 years (36.1%), female (67.2%), Catholics, coming from the capital with low education leveis. The major difficulty in applying the protocol was related to position change in the dawn reported by 42.6% of caregivers. The survival rate of appearance of PU was similar in both groups showing a peak in ten days. In 20 days of monitoring PU appeared in 32 patients of EG and 58 patients of CG. The highest incidence of PU was in the sacral region in both groups. Of the events that occurred in EG PU 53.1% were in stage I and there was no event in stage IV. As for the GC were 39.7% of the UPP Stage II and 20.7% in stage IV. Appearance of PU in more than one location occurred in 9.8% in the EG and 77% in CG. Related to the implementation of the Ayello protocol to actions applied with ease was related to inspection of the skin during bathing and the use of rollers, pads and pillows in the counterpart considered more difficult to be executed was related to the position change. Did not appeared PU whom had at least 201 changes in position in 20 days. It is póssible to assert that the Ayello’s teaching protocol for the prevention of PU, is effective as a predictive tool of prevention of PU in person with spinal cord injury.